Immunotherapy for head and neck cancer: latest developments and clinical potential - Bauml, Joshua M. (Ther Adv Med Oncol, 2016)
Head and neck squamous cell cancer (HNSCC) is a malignancy with a rapidly changing demographic profile, given the recent epidemic of human papilloma virus related cancers. Most patients present with locally advanced disease and receive combination therapeutic approaches with curative potential, albeit with significant toxicity. Up to a third of patients, however, will eventually develop recurrent or metastatic disease. The prognosis of such patients is dismal, as palliative treatment options remain limited. Immune-directed therapies offer a novel therapeutic strategy beyond cytotoxic chemotherapy and are currently being evaluated in a wide variety of malignancies. HNSCC is a particularly favorable disease for immunotherapy, as immune evasion and dysregulation have been shown to play a key role in the initiation and progression of HNSCC. This review focuses on the latest developments in immunotherapy in HNSCC, with a particular focus on checkpoint inhibitors, adoptive cellular therapies, and vaccines.